Synthesis of TiB2-reinforced iron-based composite coating - Yilmaz, S. O.; Ozenbas, M.; Yaz, M. (Elsevier Sci Ltd, 2009)
Titanium diboride (TiB2) particulate reinforced Fe-based alloy composite coating was produced with ferrotitaniurn (FeTi), ferroboron (FeB), ferrotungsten (FeW), ferrochromium (FeCr), ferrovanadium (FeV) and ferromolybdenum (FeMo) powders by using gas tungsten arc welding (GTAW) process. The effects of GTAW processing on the microstructure of AISI-4340 alloy coating with ferro-alloy powders were investigated experimentally. Abrasive wear tests were performed on the coated surface of samples to examine the influence of vol% and the size of boride on wear rates. Depending on the results, it was seen that the samples coated by FeTi-FeW-FeB ferro-alloy powders mixture have the highest wear resistance. Crown Copyright (C) 2009 Published by Elsevier Ltd. All rights reserved.
Keywords: Surface coating; GTAW; Iron based composites; TiB2; Wear resistance